Principles of translational science in medicine: from bench to bedside - Wehling, Martin (Elsevier Science & Technology, 2021)
Front Cover -- Principles of Translational Science in Medicine -- Copyright Page -- Contents -- List of contributors -- I. Introduction -- 1 Introduction and definitions -- What is translational medicine? -- Primary translation versus secondary translation -- The history of translational medicine, obstacles, and remits -- References -- 2 Problems, challenges, and initiatives in translation -- Attrition -- What translational medicine can and cannot do -- The present status of translational medicine (initiatives and deficiencies) -- New pathways to discovery -- Research teams of the future -- Reengineering the clinical research enterprise -- Translational science in medicine: the current challenge -- References -- II. Target identification and validation -- 3 "Omics" translation: a challenge for laboratory medicine -- Introduction -- "Omics": what does it mean? -- Proteomics as a paradigm of problems in translational medicine -- Development of biomarkers: from discovery to clinical application -- Discovery -- Identification/characterization -- Validation -- Standardization/harmonization -- Clinical association and clinical benefit -- Translating omics into clinical practice -- Continuum of translation research and omics -- Conclusions -- References -- 4 The power of genomics, metabolomics, and other omics for target identification and validation -- Introduction -- Genomics -- Genomic tools -- Sequencing -- Sequencing by ligation -- Sequencing by synthesis -- Arrays -- Oligonucleotide microarrays -- cDNA microarrays -- Quantitative reverse transcription polymerase chain reaction and low-density arrays -- Applications of genomics in molecular medicine -- Molecular diagnostics -- Pharmacogenomics -- Metabolomics -- Metabolomics or metabonomics? -- Metabolite profiling -- Metabolite fingerprinting -- Metabolic footprinting.